QUALITY CONTROL OF LOGS IN SEMI-MECHANIZED HARVEST - Rotili, Wilson Orlando; BRANDELERO, CATIZE; Fortes, Fabiano de Oliveira; Peripolli, Jairo Luis Zanon; de Vargas, Francieli; Werner, Valmir (Floresta, 2022)
Qualitative logging must be carried out on the semi-mechanized harvest to result in correct logs for the standard measures. This avoids waste and meets the demand of the clients, so management and monitoring of the execution of the logging activity are paramount. The objective of this study was to develop and test in loco a method to control the assertiveness of the lengths of logs, sectioned in a semi-mechanized manner. The method was applied in a stand of Eucalyptus sp., with a 20- year forest management cycle. The survey was divided into four action plans, with biweekly (PQ0, PQ1, PQ2, PQ3 e PQ4) monitoring of activities where PQ0 was for scenario recognition, and PQ1 to PQ4 were for the application of actions and measurement of logs and the classification according to levels (correct, acceptable, alarming, critical and unacceptable). It was observed the improvement of the percentages of the correct and acceptable levels, already in the first fortnight. The control method aided in minimizing failures and waste. It was found that after the application of the method avoided the loss of 0.73% of the total volume of the harvested and processed wood.